2009
DOI: 10.1117/1.3259361
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body three-dimensional optoacoustic tomography system for small animals

Abstract: Abstract. We develop a system for three-dimensional whole-body optoacoustic tomography of small animals for applications in preclinical research. The tomographic images are obtained while the objects of study ͑phantoms or mice͒ are rotated within a sphere outlined by a concave arc-shaped array of 64 piezocomposite transducers. Two pulsed lasers operating in the near-IR spectral range ͑755 and 1064 nm͒ with an average pulsed energy of about 100 mJ, a repetition rate of 10 Hz, and a pulse duration of 15 to 75 ns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
251
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(255 citation statements)
references
References 35 publications
3
251
0
1
Order By: Relevance
“…Currently optoacoustic tomography systems using 2 lasers operating in the near-IR spectral range (755 and 1064 nm) allow 3D imaging of individual organs and blood vessels through the entire body in animal models [25]. This novel method, in the future, would open a new era for imaging for human body.…”
Section: Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently optoacoustic tomography systems using 2 lasers operating in the near-IR spectral range (755 and 1064 nm) allow 3D imaging of individual organs and blood vessels through the entire body in animal models [25]. This novel method, in the future, would open a new era for imaging for human body.…”
Section: Reflectionmentioning
confidence: 99%
“…In order not to exceed limits to manufacturing technologies and keep the context as predetermined, rather giving detailed opto-electric physics; briefly the laser-matter interaction can be defined as the same in tissue-laser interaction. In addition to photothermal, photochemical and photomechanic effects laser energy may have photomagnetic effect on materials [25]. Similarly, the interaction is closely related with wavelength -matter reflectivity relation, produced temperature, present surface films, angle of incidence and surface roughness, besides laser beam (power settings, time, shot intervals, focusing, etc.)…”
Section: Laser -Matter Interactionmentioning
confidence: 99%
“…Due to the system cost and complexity when employing a large number of data acquisition (DAQ) channels, currently most PA imaging systems utilize a single-element ultrasound (US) transducer [7][8][9][10] or a one-dimensional (1-D) array US probe. [4][5][6]11 Mechanical scanning of the US probe required by these systems to form 3-D PA images limits the volumetric imaging frame rate. Thus, 3-D PA imaging systems using 2-D array US probes have been recently studied.…”
Section: Introductionmentioning
confidence: 99%
“…PA imaging, however, provides a high ultrasonic spatial resolution for deep imaging by utilizing ultrasonic detection of the PA wave generated by absorbed diffuse light. 2,3 Deep PA imaging has been used to image both biological structure (e.g., internal organs, 4,5 and sentinel lymph nodes 6 ) and function (e.g., tumor hypoxia, 7 and brain oxygenation 8,9 ). The ability of PA imaging (PA microscopy and PA computed tomography 1 ) systems to render three-dimensional (3-D) volumetric images relies on recording the PA time-of-flight signals on a two-dimensional (2-D) surface facing the photoacoustic source, light-absorbing chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, developing an Immunosensor depends on immobilization of antibody molecules, which becomes an important factor for successful fabrication of immunosensors [17], which involves screen printing technology. Photoacoustic imaging technique has been developed which works on ultrasound spatial resolution and intrinsic rich optical contrast, penetrates deep into the tissues [18,19] with acoustic ultra sounds and act as a detection tool in diagnostic medicine [20]. Thomas et al [21], demonstrated all aspects of overhand throwing, using a 12 camera Vicon motion analysis system in a general motor program using bio-electronic signals.…”
Section: Introductionmentioning
confidence: 99%